A CONTROL STUDY OF YAVAKSHARA IN THE MANAGEMENT OF BENIGN PROSTATIC HYPERPLASIA (BPH) W.S.R. TO VATASHTHEELA - M. Borkar, Kanchan; V. Shekokar, Anantkumar; Kumar Singh, Ashish (International Journal of Ayurveda and Pharma Research, 2015)
In Ayuraveda, Vatashtheela is one among the 12 types of Mutraghata (obstructive uropathy) disorders elaborated in the Sushruta Samhita. Vatashtheela disease closely resembles Benign Prostatic Hyperplasia (BPH) of modern medicine in its signs and symptoms. The control study has been carried out in two different groups. Each group made of 30 patients. In trial group 30 patients treated with Yavakshara. In control group 30 patients were treated with capsule Pyginal. It contains Pygeum Africanum which is useful in BPH. Phytotherapy refers to use of plant extract, which is popular in Europe as a herbal medicine for many years & also mentioned in modern text book of smith urology & commonly practiced by allopathic urologist. Patient was selected randomly irrespective of their religion, race, occupation etc. In BPH irritative and obstructive symptoms like frequency, urgency, staining, weak stream, incomplete emptying, nocturia, residual urine and uroflow rate were observed over the month of treatment from onset of treatment. Observations were made & results were analyzed with the help of unpaired t test at 0.05 level of significance.